2016
DOI: 10.3389/fmars.2016.00077
|View full text |Cite
|
Sign up to set email alerts
|

Disease Prevalence and Snail Predation Associated with Swell-Generated Damage on the Threatened Coral, Acropora palmata (Lamarck)

Abstract: Disturbances such as tropical storms cause coral mortality and reduce coral cover as a direct result of physical damage. Storms can be one of the most important disturbances in coral reef ecosystems, and it is crucial to understand their long-term impacts on coral populations. The primary objective of this study was to determine trends in disease prevalence and snail predation on damaged and undamaged colonies of the threatened coral species, Acropora palmata, following an episode of heavy ocean swells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…At Curaçao, it was the most common host coral species, whereas P. strigosa ranked second (Potkamp 2016). The elkhorn coral, Acropora palmata (Lamarck, 1816), is known as a common prey of Coralliophila snails (Baums et al 2003a;Miller 2001;Johnston et al 2012;Bright et al 2016). However, its abundance in Curaçao has strongly declined over the last decades (Chamberland et al 2015), which made it unsuitable as possible host in the present study.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…At Curaçao, it was the most common host coral species, whereas P. strigosa ranked second (Potkamp 2016). The elkhorn coral, Acropora palmata (Lamarck, 1816), is known as a common prey of Coralliophila snails (Baums et al 2003a;Miller 2001;Johnston et al 2012;Bright et al 2016). However, its abundance in Curaçao has strongly declined over the last decades (Chamberland et al 2015), which made it unsuitable as possible host in the present study.…”
Section: Introductionmentioning
confidence: 67%
“…and Orbicella spp. (Miller 2001;Baums et al 2003a, b;Johnston and Miller 2006;Bright et al 2016), or have grouped many host species together (Bruckner et al 1997). However, the host range on which Caribbean Coralliophila spp.…”
Section: Discussionmentioning
confidence: 99%
“…Increased occurrence and prevalence of fireworm and snail predation toward the end of the study could be severely damaging for the future growth of the species because predation may become more focused due to the lack of tissue available, leading to the removal of more growth tips from the same colonies. Moreover, fireworms have been a proven vector of a bleaching pathogen (Sussman et al, 2003), which is of great concern because colonies with predation lesions may be more likely to become diseased (Miller et al, 2014b) and both fireworms and snails have been associated with increased disease prevalence (Knowlton et al, 1990;Miller et al, 2014b;Bright et al, 2016). Therefore, it may be advantageous to manage both snail and fireworm populations to increase the health and growth of A. cervicornis.…”
Section: Discussionmentioning
confidence: 99%
“…Instrument observations on the northern Puerto Rican shelf at a leeward shelf edge bank 39.5 m depth showed that long-period swell of greater than 13 s and wave heights >4 m caused notable benthic turbulence (Bright et al, 2016). Both Hurricane Hugo and Hurricane Marilyn that passed within 25 years prior to the study were sufficiently strong to generate sea states predicted for a major storm in our calculations.…”
Section: Mechanical Disturbance As a Structuring Forcementioning
confidence: 75%